Increasing Intensive Management of Goats in the Coastal City of Kendari - Hafid, Harapin; Aku, Achmad Selamet; Aslan, La Ode M.; Ananda, Siti Hadrayanti; Harianto, Eko (Journal of Saintech Transfer, 2023)
This activity is a community service activity carried out to help increase the productivity of goat selling breeders around the coast of Kendari City, especially in the Anduonohu Market area. Implementation of activities carried out in the form of counseling in the form of visits, delivery of material and discussions directly to goat farmer. The material presented was in the form of planting forage as the main source of feed for goats and using reinforcing feed, the need for strong and tidy goat pens, namely a stage model so that they can maintain environmental cleanliness and livestock health, Management of goat manure waste into bokashi fertilizer. The results of the activity show that they understand and are capable of cultivating forage as the main source of feed and know the importance of using forage boosters (concentrates). 2) Farmers know the benefits of using stilt pens to maintain a clean environment and goat health but have not implemented them due to limited funds to build cages. 3) Farmers do not know about the use of EM4 in leftover feed and livestock manure to produce bokashi organic fertilizer in a short time.